Effect of Adding Different Concentrations of Alcohol Extracted Ginger as Feed Supplementation on Some Productive Traits of Broiler Chicken Ross Strain (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was conducted in the poultry field that belongs to Animal Production Techniques Department / Al musiab Technical College. To investigate the effect of alcohol extracted ginger supplementation in the diet on some productive traits of broiler chicken ross strain. Two hundred fifty unsexed broiler chicks were equally divided into the five groups, 50 chicks per group, 2 replicates per group (25 chicks per replicate). Chicks were fed on starter diet (1 day- 3 week) and final diet (4-6 week), diets supplemented with five ratios from alcohol extracted ginger (0, 150, 200, 250, 300 mg/kg), the first group was control but the other represented experimental groups.Results showed a significantly improve (P≤0.05) of average live body weight, weight gain, feed conversion ratio and dressing percentage in birds supplemented with alcohol extracted ginger as compared with control group at three and six weeks of birds age. As supplementation of alcohol extracted ginger had significantly (P≤0.05) decreased feed consumption and mortality ratio in experimental groups as compared with the control group.          It can be concluded that supplementation of alcohol extracted ginger to the diet had a positive effect to enhance productive traits of broiler chicken ross strain.